Perkawinan Dalam Perspektif Hukum Adat Bali - I KOMANG KAWI ARTA; I Ketut Satria Wiradharma Sumertajaya; I Gede Arya Wira Sena (Fakultas Hukum Universitas Ngurah Rai, 2025)
According to Balinese customary law which is based on Hindu religious law, there are forms of marriage that have their own uniqueness and these types of marriages are not regulated in Law Number 1 of 1974 as amended by Law Number 16 of 2019 concerning marriage. The forms of marriage that are currently still developing in Bali are ordinary marriage, nyeburin/nyentana marriage, marriage in Gelahang, inter-caste marriage. The marriage is valid after the mebyakala ceremony is carried out, while other ceremonies are considered additional. Marriage from the perspective of Balinese customary law is that a marriage will give birth to kinship and customary relations. In Balinese customary society, it is more directed towards a patrilineal kinship system, meaning a straight line of descent from the male side (Purusa) who is the successor to the family.